Harnessing of non-fibrous textile for production of high performance easy-care cotton fabrics. Issue 2 (22nd October 2018) - Mostafa, Kh.M.; Ameen, Heba; Morsy, Mahmoud; El-Ebissy, Amal; Adel, Mohamed; Salah, Ali
Abstract : Purpose: This study aims to explore the incorporation of starch nanoparticles (SNPs) in cross-linking formulation of cotton fabrics to see their impact on fabric performance like tensile strength, dry wrinkle recovery angles, elongation at break, degree of whiteness and increase in weight as well as durability. Design/methodology/approach: SNPs of size around 80-100 nm were successfully prepared from native maize starch by Nano precipitation technique and confirmed instrumentally by scanning electron microscope (SEM), transmittance electron microscope (TEM), Fourier transformer infrared (FTIR) spectroscopy and particle size analyzer. The latter were incorporated in cross-linking formulation of cotton fabrics encompassing different concentrations of citric acid and sodium hypophosphite at different curing time and temperature in 100 ml distilled water to a wet pickup of ca. 85 per cent. The fabric samples were dried for 3 min at 85°C and cured at specified temperatures for a specified time intervals in thermo fixing oven according to pad-dry-cure method. Findings: FTIR spectra and SEM micrograph signified the chemical structure and surface morphology of cotton fabric before and after finishing in absence and presence of SNPs. Cotton fabric samples finished in presence of SNPs showed a higher tensile strength, elongation at break, comparable dry wrinkle recovery angles and degree of whiteness than that finished in their absence. On the other hand, the enhancement in the aforementioned performance reflects the positive impact of incorporation of SNPs in textile finishing especially with strength properties; which are one of the important requirements for industrial fabrics that can be used widely in heavy-duty applications. Research limitations/implications: SNPs with its booming effect with respect to biodegradability, reactivity and higher surface area can be used as a novel reinforcement permanent finish for cotton fabrics instead of more hazardous materials likes poly acrylate and monomeric compounds. Practical implications: As SNPs biopolymers is one of the important reinforcement agents, so it was expected that it would minimize the great loss in strength properties during easy-care cotton finishing and improve the fabric performance. Originality/value: The novelty addressed here is undertaken with a view to remediate some of the serious defects of easy-care cotton fabrics using poly carboxylic acids; especially with the great loss in strength properties by virtue of using SNPs as a permanent finish. Besides, to the authors' knowledge, there is no published work so far concerning the use of SNPs as an innovative base for production of easy-care finished cotton textiles with high performance.